Attitudes of clinical care specialist nurses about nursing research - Stojanović Jovanović, Biljana N. (Education and Research in Health Sciences, 2023)
Introduction: Research in nursing today has a major impact on current and future nursing practice.The aim was to examine the attitudes of nurses towards research in nursing, after completing their specialization of clinical care.Methods: The study involved 86 nurses - specialists in clinical care. The instrument used in the research was a modified version of the Boot nurses' attitudes scale about the research, which consists of subscales: Interest and support of the workplace environment, Cost-effectiveness and benefits, and difficulties.Results: The highest average score was recorded in the statement "I would like to conduct research," while the lowest in the statement "I believe that my job provides the time required to conduct the research." (subscale Interest and support of the workplace environment). The highest score was recorded in the statement "The research results are useful for better health care of patients and can be applied in my workplace environment," while the lowest in claims " Nurses receive praise from their associates and colleagues when they conduct research" (Cost-effectiveness and benefit subscale). On the subscale Obstacles, the highest average result was recorded in the statement "Obtaining consent from the patient for the research implementation is very difficult," while the lowest in the statement "Research in nursing should be conducted by nurses with a completed doctorate degree."Conclusion: According to the statements of clinical care specialist nurses, there is certain interest in participating in research activities, but there is a lack of free time for research.
Keywords: attitudes; nursing; research